Emerging Role of IL-17 in Atherosclerosis - Chen, Shuang (S. Karger AG, 2010)
The IL-23-IL-17 axis is emerging as a critical regulatory system that bridges the innate and adaptive arms of the immune system. Th17 cells have been linked to the pathogenesis of several chronic inflammatory and autoimmune diseases. However, the role of Th17 cells and IL-17 in various stages of atherogenesis remains poorly understood and is only beginning to be elucidated. While IL-17 is a predominantly proinflammatory cytokine, it has a pleiotropic function and it has been implicated both as an instigator in the pathogenesis of several inflammatory disorders as well as being protective in certain inflammatory disease models. Therefore, it is not surprising that the current literature is conflicting on the role of IL-17 during atherosclerotic lesion development. Various approaches have been used by several groups to discern the involvement of IL-17 in atherosclerosis. While one study found that IL-17 is protective against atherosclerosis, several other recent studies have suggested that IL-17 plays a proatherogenic role. Thus, the function of IL-17 remains controversial and awaits more direct studies to address the issue. In this review, we will highlight all the latest studies involving IL-17 and atherosclerosis, including both clinical and experimental research.